Tindakan Lawful Interception oleh Penyidik dalam Penegakan Hukum - elda azizah putri; Rahayu, Sri; Lasmadi, Sahur (Faculty of Law, Universitas Jambi, 2025)
The rapid development of information technology has given rise to various legal issues, one of which is related to the practice of lawful interception or wiretapping carried out by law enforcement officers. This practice often raises debate because it has the potential to violate citizens' privacy rights, which are part of human rights. This study aims to analyze the limitations of investigators' authority in conducting lawful interception and examine the legal regulations governing such actions in Indonesia, particularly in the context of law enforcement and human rights protection. The research method used is normative juridical, with a statutory, conceptual, historical, and case approach. The theoretical basis used is legal certainty, legal protection and criminal law policy. The results of the study show that the regulation of lawful interception in Indonesia has been spread across various laws and regulations, such as Law Number 1 of 2024 concerning Information and Electronic Transactions and Law Number 19 of 2016, but there is no comprehensive regulation that clearly regulates the procedures, mechanisms, and limitations of investigators' authority in conducting wiretapping. ABSTRAK Perkembangan teknologi informasi yang pesat telah memunculkan berbagai permasalahan hukum, salah satunya terkait praktik lawful interception atau penyadapan yang dilakukan aparat penegak hukum. Praktik ini sering kali menimbulkan perdebatan karena berpotensi melanggar hak privasi warga negara, yang merupakan bagian dari hak asasi manusia. Penelitian ini bertujuan untuk menganalisis batasan kewenangan penyidik dalam melakukan lawful interception serta menelaah pengaturan hukum yang mengatur tindakan tersebut di Indonesia, khususnya dalam konteks penegakan hukum dan perlindungan hak asasi manusia. Metode penelitian yang digunakan adalah yuridis normatif, dengan pendekatan perundang-undangan, konseptual, historis, dan kasus. Landasan teori yang digunakan adalah kepastian hukum, perlindungan hukum dan kebijakan hukum pidana. Hasil penelitian menunjukkan bahwa pengaturan lawful interception di Indonesia telah tersebar dalam berbagai peraturan perundang-undangan, seperti Undang-Undang Nomor 1 Tahun 2024 tentang Informasi dan Transaksi Elektronik serta Undang-Undang Nomor 19 Tahun 2016, namun belum ada regulasi yang komprehensif yang mengatur secara jelas prosedur, mekanisme, dan batasan kewenangan penyidik dalam melakukan penyadapan.